Implementation of Search Engine Optimalization (SEO) on the Village-Owned Enterprises Luhur Sembada Website - Mukhamad Nur Cahyo; Nur'aini Nur'aini (Universitas Hamzanwadi, 2022)
Luhur Sembada Village-Owned Enterprises (LSVOE) purpose to develop various business units to realize the welfare of the people of the Kalurahan Sidoluhur community through productive economic development efforts. However, the sales media run is ineffective and efficient because the information system is still managed manually. This study aims to facilitate all information and product sales in the LSVOE so that it can be known through a website-based information system and apply SEO techniques to increase the reach of sales promotion on the website. Data collection are carried out through observation, interviews, and literature studies. This research uses the system development life cycle method for website creation and applies On Page and Off Page SEO techniques. This research resulted in the website of the information system of the LSVOE, which was first tested using black bock testing. In addition, this research resulted in website development using technical SEO, which was first tested using web.dev and page speed. The website that has been designed has successfully entered page one of the Google search and is easily searched by the wider community. A website-based information system can expand information on the productive economic development of the LSVOE and help improve website promotion.